Neurobiological Bases of the Use of Atypical Antipsychotics in Treatment-Resistant Major Depressive Disorder - Kirby, Julia (Université d'Ottawa / University of Ottawa, 2018)
Only one third of depressed patients experience a beneficial therapeutic effect after using a first-line medication, leaving two-thirds of patients without effective treatment. It has been shown that a combination of two drugs with different modes of action result in an increase in the number of patients responding to treatment. One of the most effective strategies is the addition of low doses of an atypical antipsychotic. In depth evaluation of the neurobiological properties of atypical antipsychotics have revealed that these agents produce antidepressant effects and enhance the therapeutic response of first-line medications through antagonism of the 5-HT2A, 5-HT2C, 5-HT1B/D, 5-HT7 receptors and NET; agonism of the 5-HT1A receptor; and/or D2/3 partial agonism. The present experiments focused on determining the mode of action of this combination of drugs to help design better antidepressant treatment in the future. A series of electrophysiological experiments were proposed to assess 5-HT and NE neurotransmission in the rat hippocampus, as well as DA transmission in the rat forebrain.
Keywords: Major Depressive Disorder; Atypical Antipsychotics; Aripiprazole; Escitalopram; Augmentation; Electrophysiology; Serotonin; Dopamine; Norepinephrine; Monoamines; Antidepressant